2013
DOI: 10.3389/fphys.2013.00011
|View full text |Cite
|
Sign up to set email alerts
|

Genetic background influences adaptation to cardiac hypertrophy and Ca2+ handling gene expression

Abstract: Genetic variability has a profound effect on the development of cardiac hypertrophy in response to stress. Consequently, using a variety of inbred mouse strains with known genetic profiles may be powerful models for studying the response to cardiovascular stress. To explore this approach we looked at male C57BL/6J and 129/SvJ mice. Hemodynamic analyses of left ventricular pressures (LVPs) indicated significant differences in 129/SvJ and C57BL/6J mice that implied altered Ca2+ handling. Specifically, 129/SvJ mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…Furthermore, the high concentration (125 mM) and dose (500 nmol/kg) of Mn ensure that Mn availability is not limiting. In addition, these results are consistent with other investigations demonstrating decreased calcium uptake in the heart following ISO treatment (57,60). Thus, the conclusion that the measured decrease in Mn uptake is a result of ISO-induced hypertrophy and not of relative changes in perfusion or Mn uptake to other organ systems remains the most parsimonious interpretation of these data.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, the high concentration (125 mM) and dose (500 nmol/kg) of Mn ensure that Mn availability is not limiting. In addition, these results are consistent with other investigations demonstrating decreased calcium uptake in the heart following ISO treatment (57,60). Thus, the conclusion that the measured decrease in Mn uptake is a result of ISO-induced hypertrophy and not of relative changes in perfusion or Mn uptake to other organ systems remains the most parsimonious interpretation of these data.…”
Section: Discussionsupporting
confidence: 93%
“… showed that 129SV/J mice differ from C57 mice in SR calcium content, left‐ventricular ejection fraction, fractional shortening and cellular volume. Previous work from our laboratory demonstrated increased sensitivity to ISO‐induced cardiac hypertrophy in 129SV/J mice, as measured by HW/BW . Although no differences between the strains were observed under baseline conditions, it is possible that increased cardiac stress caused by exercise or positive inotropic stimulation (e.g.…”
Section: Discussionmentioning
confidence: 78%
“…Although rodent strain selection has always been part of any study design, the increased availability and use of genetically modified rodents, particularly mice, as model systems for human diseases has revolutionized the way we conduct research in general while increasing awareness about the influence of genetic background on the resulting phenotype, which encompasses the cardiac phenotype. For example, many studies have reported mouse strain variations for cardiac function, 38,39 response to β-adrenergic stimulation 40 and angiotensin II, 41 and capacity for calcium handling, 42,43 but also for susceptibility to specific pathophysiological states, such as myocardial hypertrophy 44,45 or heart failure. 46 In terms of cardiac metabolism, only a few studies have made a systematic comparison among commonly used control mouse strains.…”
Section: General Methodological Considerationsmentioning
confidence: 99%
“…Thus, this difference in the genetic background most likely explains the discrepancies between their and our studies (Crawley et al ., ; Kiselycznyk & Holmes, ). Furthermore, increasing evidence suggests that there are prominent differences in the performance in behavioural tasks, the pattern of protein expression and synaptic physiology among various mouse strains (Waters et al ., ; Lenselink et al ., ; Rubenstein et al ., ; Zhang et al ., ).…”
Section: Discussionmentioning
confidence: 99%